Two new species of Sweltsa (Plecoptera: Chloroperlidae) from China - Li, Wenliang; Wang, Yingying; Li, Weihai; Li, Mengyu (Zootaxa, 2021)
Two new species of the genus Sweltsa Ricker, 1943 from Zhejiang Province, China are described and compared with similar species. The new species are Swelsta bicurvata Li, W.L. & Li, W.H. sp. nov. and Sweltsa zhejiangensis Li, W.H. & Wang, sp. nov.